Platelets as Mediators of Neuroinflammation and Thrombosis - Rawish, Elias; Nording, Henry; Münte, Thomas; Langer, Harald F. (Frontiers in Immunology, 2020)
Beyond platelets function in hemostasis, there is emerging evidence to suggest that platelets contribute crucially to inflammation and immune responses. Therefore, considering the detrimental role of inflammatory conditions in severe neurological disorders such as multiple sclerosis or stroke, this review outlines platelets involvement in neuroinflammation. For this, distinct mechanisms of platelet-mediated thrombosis and inflammation are portrayed, focusing on the interaction of platelet receptors with other immune cells as well as brain endothelial cells. Furthermore, we draw attention to the intimate interplay between platelets and the complement system as well as between platelets and plasmatic coagulation factors in the course of neuroinflammation. Following the thorough exposition of preclinical approaches which aim at ameliorating disease severity after inducing experimental autoimmune encephalomyelitis (a counterpart of multiple sclerosis in mice) or brain ischemia-reperfusion injury, the clinical relevance of platelet-mediated neuroinflammation is addressed. Thus, current as well as future propitious translational and clinical strategies for the treatment of neuro-inflammatory diseases by affecting platelet function are illustrated, emphasizing that targeting platelet-mediated neuroinflammation could become an efficient adjunct therapy to mitigate disease severity of multiple sclerosis or stroke associated brain injury.